Islands of hope : indigenous resource management in a changing pacific - D'Arcy, Paul; Kuan, Da-wei (Pacific Series., 2023)
"In the Pacific, as elsewhere, Indigenous communities live with the consequences of environmental mismanagement and over-exploitation but rarely benefit from the short-term economic profits such actions may generate within the global system. National and international policy frameworks ultimately rely on local community assent. Without effective local participation and partnership, these extremely imposed frameworks miss out on millennia of local observation and understanding and seldom deliver viable and sustained environmental, cultural and economic benefits at the local level. This collection argues that environmental sustainability, indigenous political empowerment and economic viability will succeed only by taking account of distinct local contexts and cultures. In this regard, these Pacific Indigenous case studies offer ‘islands of hope’ for all communities marginalised by increasingly intrusive—and increasingly rapid—technological changes and by global dietary, economic, political and military forces with whom they have no direct contact or influence." - taken from publisher website.